2022
DOI: 10.1111/tpj.15902
|View full text |Cite
|
Sign up to set email alerts
|

Orthology‐based analysis helps map evolutionary diversification and predict substrate class use of BAHD acyltransferases

Abstract: SUMMARY Large enzyme families catalyze metabolic diversification by virtue of their ability to use diverse chemical scaffolds. How enzyme families attain such functional diversity is not clear. Furthermore, duplication and promiscuity in such enzyme families limits their functional prediction, which has produced a burgeoning set of incompletely annotated genes in plant genomes. Here, we address these challenges using BAHD acyltransferases as a model. This fast‐evolving family expanded drastically in land plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Both training and complete BAHDome sets were used to understand different phylogenetic and functional traits of the BAHD acyltransferase superfamily. In general, the topology of the phylogenetic reconstruction generated (both with training and complete BAHDome sets) agree with others published elsewhere [21], [24]. These studies were dedicated to few species and, since they were mostly based on characterized BAHD enzymes, the complete BAHDome space was not extensively covered.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Both training and complete BAHDome sets were used to understand different phylogenetic and functional traits of the BAHD acyltransferase superfamily. In general, the topology of the phylogenetic reconstruction generated (both with training and complete BAHDome sets) agree with others published elsewhere [21], [24]. These studies were dedicated to few species and, since they were mostly based on characterized BAHD enzymes, the complete BAHDome space was not extensively covered.…”
Section: Discussionsupporting
confidence: 86%
“…These sites implicate an evolutionary advantage towards promiscuity and eventually functional diversification. In addition, a recent study identified residues W36 and C320 in Dm3MaT3 as key for the enzyme's activity [24]. This enzyme corresponds to A4PHY4 from Chrysanthemum morifolium in our dataset, which belongs to G2, and we indeed identified both these positions as SDPs (corresponding to SDPs 31 and 302) in different analyses.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To identify montbretia enzymes involved in the biosynthesis of caffeic acid and caffeoyl-CoA, we used BLASTP searches against a translated transcriptome database that covers a time course of corm development, previously described in Irmisch et al (2020). Known plant HCT sequences typically belong to Clade 5 of the BAHD acyltransferase (AT) family (Kruse et al, 2022(Kruse et al, , 2023Moghe et al, 2023). A search of the montbretia transcriptome using A. thaliana HCT (NP_199704.1) revealed three candidate genes, for which we cloned the coding sequences (CDS) from young corms.…”
Section: Identification Of Montbretia Hct Candidatesmentioning
confidence: 99%
“…Ni-affinity purified proteins (Figure S9) were used for enzyme assays, and products were identified based on accurate mass and authentic standards. CcAT8 was assayed with the acyl acceptor shikimate or quinate, and one of the acyl donors caffeoyl-, coumaroyl-, or feruloyl-CoA, which are substrates typically used by HCTs from other plant species (Kruse et al, 2022(Kruse et al, , 2023Moghe et al, 2023). With shikimate as the acyl acceptor, all three acyl-CoA donors were converted into the respective shikimate esters, caffeoylshikimate (m/z 335.0893), coumaroylshikimate (m/z 319.0807) and feruloylshikimate (m/z 349.0932) (Figure 4).…”
Section: In Vitro Enzyme Activities Support Ccat8 As Bona Fide Cchct ...mentioning
confidence: 99%